KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK FARMASI BANDA ACEH TAHUN PELAJARAN 2019/2020 - IRMA ROSITA (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
Based on the results of observations that the authors conducted at the Pharmacy Vocational High School in Banda Aceh, the managerial competence of the principal is a strategy to improve the quality of education in educational institutions (schools). If the managerial competence of the principal is good, it will be able to improve the quality of the school. This study aims to find out an overview of: planning school programs, fostering students, creating fun learning, organizing school administration, and fostering and implementing cooperation with the drug industry. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observation and documentation studies. The research subjects were principals and teachers at the Pharmacy Vocational School in Banda Aceh. The results of the study show that: (1) The principal at the Pharmacy Vocational School in Banda Aceh has the managerial ability to mobilize staff, teachers and employees, as well as optimize school resources and support students in a good learning process. (2) The principal in improving the quality has expertise in planning, implementing and evaluating programs that have been made together, as well as creating fun learning for students in the teaching and learning process, as well as receiving suggestions and criticisms from subordinates and communicating about policies and problems together. (3) The principal's conceptual skills in improving the quality of education, especially in the Pharmacy Vocational School of Banda Aceh. The principal clearly plans the program and implements learning and evaluates, in accordance with the vision, mission and objectives of the Banda Aceh Pharmacy Vocational High School. Keywords: Principal Managerial Competence, Education Quality